State health disparities research in Rural America: Gaps and future directions in an era of COVID‐19. Issue 3 (21st April 2021) - Cacari Stone, Lisa; Roary, Mary C.; Diana, Augusto; Grady, Patricia A.
Abstract: Purpose: In an era of the COVID‐19 pandemic, improving health outcomes for diverse rural communities requires collective and sustained actions across transdisciplinary researchers, intersectoral partners, multilevel government action, and authentic engagement with those who carry the burden—rural communities. Methods: Drawing from an analysis of transcriptions and documents from a national workshop on the "State of Rural Health Disparities: Research Gaps and Recommendations, " this brief report underscores the gaps and priorities for future strategies for tackling persistent rural health inequities. Findings: Four overarching recommendations were provided by national thought leaders in rural health: (1) create mechanisms to allow the rural research community time to build sustainable community‐based participatory relationships; (2) support innovative research designs and approaches relevant to rural settings; (3) sustain effective interventions relevant to unique challenges in rural areas; and (4) recognize and identify the diversity within and across rural populations and adapt culturally and language‐appropriate approaches. Conclusion: The COVID‐19 public health crisis has exacerbated disparities for rural communities and underscored the need for diverse community‐centered approaches in health research and dedicated funding to rural service agencies and populations.